Wokół teorii młodzieży pogranicza wschodniego = Around the theories of the youth from the eastern borderlands - Długosz, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article was to present the empirical and theoretical knowledge on the topic of the youth from the Eastern Borderlands. The authors attempted to provide the characteristics of the youth concerned and explain the noticed qualities. The empirical data concerning the young generation come from the surveys conducted between 2007 and 2017. The material gathered from seven surveys shows that the youth from the borderlands use conventional strategies of entering adulthood. In social life, they are driven by meritocratic rules. They base their future on tertiary education at prestigious universities outside the region. The borderlands are not attractive for living and majority of the researched intend to leave their place of residence and move to a metropolis or abroad. As a consequence of youth emigration, the borderlands will be deprived of the endogenic sources of social development.
Keywords: młodzież; pogranicze wschodnie; plany życiowe; aspiracje edukacyjne; youth; Eastern Borderlands; life plans; educational aspirations; emigration